Erythropoietin stimulates a rise in intracellular free calcium concentration in single early human erythroid precursors. - Miller, B A (1988)
Erythropoietin and granulocyte-macrophage colony-stimulating factor (GM-CSF) stimulate the differentiation and proliferation of erythroid cells. To determine the cellular mechanism of action of these growth factors, we measured changes in intracellular free calcium concentration [( Cac]) in single human erythroid precursors in response to recombinant erythropoietin and GM-CSF. [Cac] in immature erythroblasts derived from cultured human cord blood erythroid progenitors was measured with fluorescence microscopy digital video imaging. When stimulated with erythropoietin, [Cac] in the majority of erythroblasts increased within 3 min, peaked at 5 min, and returned toward baseline at 10 min. The percentage of cells that responded to erythropoietin stimulation increased in a dose-dependent manner. Additional stimulation with GM-CSF in cells previously exposed to erythropoietin resulted in a second [Cac] increase. Immature erythroblasts treated with GM-CSF followed by erythropoietin responded similarly to each factor with a rise in [Cac]. The source of transient calcium is intracellular since erythroblasts were incubated in medium devoid of extracellular calcium. Our observations suggest that changes in [Cac] may be an intracellular signal that mediates the proliferative/differentiating effect of hematopoietic growth factors.